Estudo sobre o processo de decisão de compra e meios de pagamentos: uma perspectiva da comunidade discente de uma Universidade Federal - Unipampa - (:unkn) unknown (Universidade Federal do Pampa, 2010)
The objective of this study is to analyze the factors that influence the purchase decision process of students from UNIPAMPA - Campus Santana do Livramento. The purpose of this research, besides seeking to understand how young university students behave when making their purchases, also aims to analyze what types of payment methods are being used more frequently by this public. Thus, in order to achieve the results of the proposed objectives, the case study was used as a research method and for this purpose a descriptive study with a quantitative approach was used, using questionnaires that were applied to the students of the five campus courses . The sample consisted of 273 randomly chosen individuals from approximately 1,200 campus students. The public's choice of mostly young college students relies on the fact that they are at the beginning of their economic life, which makes it easier to assemble the profile of these students. As a general observation of the research results, and taking into account the limitations included in the method, it was noticed that the majority of university students depend financially on the parents, are single and of the female gender, regarding the use of credit card, it was verified that The use of this medium is growing in this public.
Study on the purchasing decision and means of payments: a perspective of the student community of a Federal University - Unipampa
Keywords: Administração; Comportamento do consumidor; Cartão de crédito: uso; CNPQ::CIENCIAS SOCIAIS APLICADAS